VEGETATION OF FRESH WATER SWAMPY AREAS IN WEST AND CENTRAL KALIMANTAN - Eizi Suzuki; Takashi Kohyama; Herwint Simbolon (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Vegetation types in fresh water swampy areas: Mandor in West Kalimantan and Lahei in Central Kalimantan, were compared.There were three types: kerangas, kerangas shrub and peat swamp forest. Kerangas forests in both areas had similar flora in some extent.That of peat swamp was very different from kerangas though both vegetations distributed in adjacent area.